San’yas Indigenous Cultural Safety Training as an Educational Intervention: Promoting Anti-Racism and Equity in Health Systems, Policies, and Practices - Browne, Annette J.; Varcoe, Colleen; Ward, Cheryl (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
The San’yas Indigenous Cultural Safety Training Program is an Indigenous-led, policy-driven, and systems-level educational intervention to foster health equity and mitigate the effects of systemic racism experienced by Indigenous people in health and other sectors. Currently, San’yas is being scaled-up across Canada. This article focuses on the following: (a) the pedagogical underpinnings of San’yas grounded in transformational learning principles and Indigenous knowledges; (b) the scope, reach, and scale-up of San’yas as an explicit anti-racism educational intervention; (c) its unique program delivery approaches; and (d) program evaluation trends. We discuss the insights gained from implementing San’yas over the past decade, which will be relevant for leaders and policy-makers concerned with implementing anti-racism educational interventions as part of broader system transformation.